Análisis preliminar de la flora vascular de los bosques mesófilos de montaña de México - Rzedowski, Jerzy (Instituto de Ecología, A.C., 1996)
The paper presents a preliminary list of 650 genera of vascular plants that contain at least one species linked in exclusive or preferential way with the montane mesophilous forest (cloud forest) of Mexico. The analysis of this inventory reveals that: a) Epiphytes show to be the best represented life form in this forest and the family Orchidaceae prevails in the number of genera, being more than twice as important as Compositae and almost four times as important as Leguminosae. b) 13 families of the vascular flora of Mexico (Brunelliaceae, Chloranthaceae, Cunoniaceae, Hamamelidaceae, Illiciaceae, Nyssaceae, Podocarpaceae, Proteaceae, Sabiaceae, Schisandraceae, Tovariaceae, Tropaeolaceae and Winteraceae) are exclusive or almost exclusive of this vegetation type and the majority of components of additional 33 families are preferential o exclusive members of the montane mesophilous forest. c) On the generic level southern affinity amply prevails over the northern one; only 2% of the genera are restricted in their distribution to the limits of the country, but this percentage rises to 12 if the joint area of Mexico and Central America is taken as reference.